Sustainable Development through the Z-Chicken Baznas Initiative: A Community-Based Approach in South Tangerang City - Setyaudin, Taufik (Fakultas Ilmu Sosial dan Ilmu Politik (FISIP),UIN Syarif Hidayatullah Jakarta, 2023)
Abstract. This research aims to find out the manifestation of economic independence within the community through the Z-Chicken program of Baznas in South Tangerang City. The program is considered as one of the efforts to enhance the welfare of the community. The research method employs a qualitative approach, involving the study of data and documents related to the Z-Chicken program of Baznas in South Tangerang City. Qualitative methods are deemed the most appropriate approach to gather information regarding the improvement of economic independence within the community through the Z-Chicken program of Baznas in South Tangerang City. The study of the Z-Chicken program in South Tangerang as an initiative to enhance the economic independence of the community reveals sustainable impacts, such as transforming beneficiaries into contributors. The presence of this empowerment program should be expanded in its reach. Furthermore, regular mentoring for beneficiaries who have gained from the Z-Chicken program in South Tangerang is essential for program evaluation and development. Keywords: Economic Independence, Z-Chicken Program, Baznas, Kota Tangerang Selatan, Mustahik, Muzakki. Abstrak. Penelitian ini memiliki tujuan untuk mencari tahu wujud dari kemandirian ekonomi masyarakat melalui program Z-Chicken Baznas Kota Tangerang Selatan. Program tersebut merupakan salah satu upaya dalam rangka meningkatkan kesejahteraan masyarakat. Penelitian ini menggunakan pendekatan metode kualitatif, yaitu dengan cara mempelajari data dan dokumen yang berhubungan dengan Program Z-Chicken Baznas Kota Tangerang Selatan. Metode kualitatif ini dianggap sebagai pendekatan yang paling tepat untuk menggali informasi mengenai peningkatkan kemandirian ekonomi masyarakat melalui program Z-Chicken Baznas Kota Tangerang Selatan. Penelitian program Z-Chicken Baznas Tangsel sebagai upaya peningkatan kemandirian ekonomi masyarakat, ternyata dapat memberikan dampak yang berkesinambungan, salah satunya mengubah mustahik jadi muzakki. Keberadaan program pemberdayaan ini harus lebih diperluas jangkauannya. Dan adanya mentoring secara berkala terhadap mustahik yang telah menerima manfaat dari program Z-Chicken Baznas Tangsel sebagai bahan evaluasi dan pengembangan program. Kata Kunci: Kemandirian Ekonomi, Program Z-Chicken, Baznas Kota Tangsel, Mustahik, Muzakki.